Digitalization of Judicial Electronic Archives using the Rational Unified Process Method with An Application Development Framework Using CodeIgniter (Case Study of Pengadilan Tinggi Agama Palembang) - Zevy Ega Foresta DS; Kurniawan Kurniawan (Journal of Information System and Informatics, 2022)
The archiving process at the Pengadilan Tinggi Agama Palembang was still manual, where archive officers must prepare storage areas, sort and classify archives, put files into folders, and create archival data. The increasing number of archives and piling up in storage space makes searching for archives difficult and takes a long time in the process of searching for the required archives. The purpose of this research is to improve the existing system by designing a web-based archiving digitization application. In this research, the system development stage uses the Rational Unified Process (RUP) method with an application development framework using CodeIgniter. Based on the test results using the blackbox testing method, the system can display information on the decision archives graphically, the archive search process quickly, downloads the decision archive documents digitally, digital documents that have been separated by archive type and archive year, so it can be concluded that the archival information system with the application of information technology can facilitate work in processing, storing, reporting to obtain information and can then be used for decision making.